Respuesta :
9u -6v = 9<-5, 1> -6<7, -4>
.. = <9*-5 -6*7, 9*1 -6*-4>
.. = <-87, 33>
.. = <9*-5 -6*7, 9*1 -6*-4>
.. = <-87, 33>
Answer:
[tex]9u-6v=\langle-87, 33\rangle[/tex]
Step-by-step explanation:
In order to sum the vector [tex]u[/tex] and the vector [tex]v[/tex] , it is convenient to define some operations.
The vector addition is given by:
[tex]u \pm v = \langle u_1 \pm v_1 , u_2\pm v_2 ,..,u_n\pm v_n\rangle[/tex]
And the scalar multiplication is given by:
[tex]ku=k \langle u_1 ,u_2,..., u_n\rangle =\langle k u_1, k u_2,..., k u_n \rangle[/tex]
Using the previous definitions, let's solve the problem.
First, let's find [tex]9u[/tex] :
[tex]9u=9 \langle -5,1 \rangle =\langle 9*(-5), 9*(1)\rangle=\langle-45, 9\rangle[/tex]
Now, let's find [tex]6v[/tex] :
[tex]6v=6\langle 7,-4 \rangle =\langle 6*(7), 6*(-4)\rangle=\langle42, -24\rangle[/tex]
Finally, let's find [tex]9u-6v[/tex]:
[tex]9u-6v=\langle-45, 9\rangle - \langle42, -24\rangle =\langle-45 -42, 9-(-24)\rangle=\langle-87, 33\rangle[/tex]